2016
DOI: 10.1200/jco.2015.63.2489
|View full text |Cite
|
Sign up to set email alerts
|

Racial Variation in the Uptake of Oncotype DX Testing for Early-Stage Breast Cancer

Abstract: Purpose Oncotype DX (ODX) is a tumor gene-profiling test that aids in adjuvant chemotherapy decision-making. ODX has the potential to improve quality of care; however, if not equally accessible across racial groups, disparities in cancer care quality may persist or worsen. We examined racial disparities in ODX testing uptake. Methods We used data from the Carolina Breast Cancer Study, phase III, a longitudinal, population-based study of 2,998 North Carolina women who received a diagnosis of breast cancer betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 34 publications
6
47
2
1
Order By: Relevance
“…In accordance with previous reports, we observed a higher probability of GEP testing in patients with an intermediate clinical risk profile: smaller tumors of low or intermediate grade without axillary lymph node involvement [11,12,13,14,15]. This finding is in itself not surprising, since in these patients most controversy exists regarding CT benefit.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with previous reports, we observed a higher probability of GEP testing in patients with an intermediate clinical risk profile: smaller tumors of low or intermediate grade without axillary lymph node involvement [11,12,13,14,15]. This finding is in itself not surprising, since in these patients most controversy exists regarding CT benefit.…”
Section: Discussionsupporting
confidence: 92%
“…We observed a higher incidence of GEP use in younger patients. Several reports endorse this finding [13,14,16], whereas others report an increased use of GEPs in patients between 50 and 69 years of age [11,15]. Since the added value of CT is inversely related with age, the observed preferential GEP use in younger women can possibly be explained by the fact that GEPs are mainly used to seek reassurance in withholding CT in these women in whom guidelines advocate administration of CT [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers on that study were able to adjust for comorbid illnesses, which they observed were more common among non-white patients(18). …”
Section: Discussionmentioning
confidence: 99%
“…2). Их экспрессия определяется среди больных с ER + / PR + , HER-2 -РМЖ без метастазов в лимфатические узлы [21]. Дан-ный набор не должен назначаться больным с HER-2 + или базальноподобным подтипами.…”
Section: диагностика о н стат иunclassified